Learning Pattern Analysis through Learning Analytics: Improving Language Learning in Ubiquitous Contexts - Safar, Muh.; Santos, Luis (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The increasing use of technology in education, particularly application-based learning, has the potential to enhance language learning. Effective language acquisition relies on analyzing learning patterns to improve student engagement and outcomes. With the growing role of learning analytics, this research explores how technology can be applied to understand and improve language learning in a broader context. Purpose. The study aims to analyze language learning patterns through learning analytics and explore how technology can contribute to enhancing language learning in various contexts. Specifically, it focuses on identifying how different learning behaviors and engagement levels influence language proficiency. Method. A quantitative research approach was used, collecting data from 200 learners who utilized language learning applications. The data were analyzed to identify patterns in user engagement and learning behaviors, focusing on the relationship between time spent on different types of learning materials and language proficiency outcomes. Results. The findings reveal that learners who spent more time engaging with conversation and writing materials generally showed better language skills. In contrast, students with basic language proficiency were found to focus more on grammar and vocabulary materials. This suggests that more advanced learners benefit from interactive, communicative tasks, while beginners need a focus on foundational elements like grammar and vocabulary. Conclusion. The study concludes that language learning is more effective when it involves social and contextual interaction, rather than relying solely on passive methods like memorization. These findings offer valuable insights for the design of language learning applications that are more adaptive to student preferences, encouraging more personalized and engaging learning experiences. The research highlights the importance of considering different learning patterns to enhance the overall effectiveness of language learning technology.